THE EFFECT OF DISCOVERY LEARNING MODEL ON SCIENCE LITERACY SKILLS OF ECOLOGICAL MATERIAL AT SMP NEGERI 1 DELITUA - Aulia, Riski; Hardinata, Aristo (ISER (Indonesian Science Education Research), 2024)
This research aims to investigate the impact of the Discovery Learning model on students' scientific literacy skills in ecology at SMP Negeri 1 Delitua. The research method used was quantitative with a sample of 66 students from classes VII-5 and VII-6, selected using a purposive sampling technique. The instrument used is a scientific literacy test, with the independent variable (Discovery Learning model and direct learning model) and the dependent variable is students' scientific literacy abilities. The results of the research show that the application of the Discovery Learning model has a significant influence on the scientific literacy abilities of class VII-5 students who are at level 2 with a score of 31, which is in the poor category. However, after implementing the Discovery Learning model, scientific literacy ability increased to level 4 with a score of 69 and was included in the sufficient category.In conclusion, the application of the Discovery Learning model is effective in improving students' literacy skills on ecological material in class VII-5 SMP Negeri 1 Delitua. This finding provides an important implication for the development of a more problem-oriented student learning approach in improving students' science literacy.